Ultra-fast generator for impact ionization triggering. Issue 1 (1st January 2023) - del Barrio Montañés, A A; Senaj, V; Kramer, T; Dutheil, Y; Sack, M
Abstract: Impact ionization triggering can be successfully applied to standard thyristors, thus boosting their dI/dt capability by up to 1000x. This ground-breaking triggering requires applying significant overvoltage on the anode-cathode of a thyristor with a slew rate > 1 kV/ns. Compact pulse generators based on commercial off-the-shelf (COTS) components would allow the spread of this technology into numerous applications, including fast kicker generators for particle accelerators. In our approach, the beginning of the triggering chain is an HV SiC MOS with an ultra-fast super-boosting gate driver. The super boosting of a 1.7 kV rated SiC MOS allows to reduce the MOS rise time by a factor of > 26 (datasheet tr = 20 ns vs. measured tr < 800 ps), resulting in an output voltage slew rate > 1 kV/ns and an amplitude > 1 kV. Additional boosting is obtained by a Marx generator with GaAs diodes, reaching an output voltage slew rate > 11 kV/ns. The final stage will be a Marx generator with medium size thyristors triggered in impact ionization mode with sufficient voltage and current rating necessary for the triggering of a high power thyristor. This paper presents the impact ionization triggering of a small size thyristor.